Novel trends and opportunities for microencapsulation of flaxseed oil in foods: A review - Kouadio Jean Eric-Parfait Kouamé (Elsevier, 2021)
The prevention and reduction of several serious diseases (Cancer, diabetes, atherosclerosis, hypertension, eczema, gastrointestinal disorders, and cardiovascular diseases) has been associated with flaxseed oil. Flaxseed oil has considerable benefits mainly related to omega-3 fatty acids, which are increasingly used in the food industry. However, many factors such as pH, temperature, oxygen, and light limit these different components (omega-3 fatty acids) to formulate many foods. In this sense, the production of functional foods requires maintaining the stability, bioactivity, and bioavailability of active compounds. Microencapsulation techniques have been developed and applied to design flaxseed oil-enriched food products to overcome these obstacles. With this in mind, this review discusses recent advances in encapsulation techniques with the incorporation of omega-3 fatty acids from flaxseed oil into food matrices. Encapsulation methods and coating materials will be presented following the literature on flaxseed and flaxseed oil composition and their health attributes. The application of flaxseed oil encapsulates in food matrices and their effect on food function will also be discussed.